Human polymorphonuclear neutrophils express RANK and are activated by its ligand, RANKL - Riegel, Alexander; Maurer, Thomas B.; Prior, Birgit; Stegmaier, Sabine; Heppert, Volkmar; Wagner, Christof; Hänsch, Gertrud Maria (European journal of immunology, 2012)
The receptor activator of NF-κB (RANK) is especially well studied in the context of bone remodeling, and RANK and its ligand, RANKL, are key molecules in the induction of bone resorbing osteoclasts. We now report that polymorphonuclear neutrophils (PMNs) contain preformed RANK, stored in secretory vesicles and in specific granules. Upon stimulation of PMNs in vitro, RANK was translocated to the cell membrane. In patients with persistent bacterial infections, RANK surface expression was enhanced compared with that of healthy individuals. The functional activity of RANK was assessed by determining migration of PMNs toward RANKL. A time- and dose-dependent migration was seen, leading to the conclusion that RANK on PMNs is functional. We presume that regulated RANK expression contributes to the fine tuning of PMN migration, for example, on and through inflamed endothelium that is known to express RANKL.